A novel astrovirus associated with encephalitis and ganglionitis in domestic sheep. Issue 3 (22nd February 2017) - Pfaff, F.; Schlottau, K.; Scholes, S.; Courtenay, A.; Hoffmann, B.; Höper, D.; Beer, M.
Summary: In June 2013, a 4‐year‐old Welsh Mountain ewe and in March 2014 a 10‐day‐old lamb of the same breed and the same flock presented progressive neurological signs including depressed sensorium, tremor, and unusual behaviour. Neuropathological examination of the brain and spinal cord detected non‐suppurative polioencephalomyelitis and dorsal root ganglionitis, characteristic of a neurotropic viral agent in both sheep. Metagenomic analysis of different tissue samples from both animals identified a novel Ovine Astrovirus (OvAstV). The presence of viral genome in the central nervous system was confirmed by RT‐qPCR. Although the cases presented nine months apart, the identified OvAstV shared nearly identical sequences, differing in only three nucleotide positions across the complete genome. Phylogenetic analysis revealed a close relation of OvAstV to neurotropic bovine astroviruses and an enteric OvAstV. In conclusion, these are the first reported cases of astrovirus infection in domestic sheep that were associated with encephalitis and ganglionitis.